Effect of Irrigation and Amino acid Application Rates in Growth and Yield of Toroh (Cucumis melo var. flexuosus) - elgubshawi, Abdelmoneim Ahmed; Attia, Hussin (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
Abstract Experiments were carried out in the Experimental Farm; Budaiya, kingdom of Bahrain, to investigate the growth and yield of snake cucumber (Cucumis melo var. flexuosus), locally known as Toroh (local variety) in relation to irrigation and foliar application of amino acid rates. Traditionally, vegetables cultivation practice throughout the country with low production contributed to 14% of demand. To improve production, several techniques adopted of which drip irrigation, chemical fertilizers, soil conditioners and plant growth regulators. In this, regard Irrigation at rates of 5L/hr for 10 min (1, 2 and 3 times/week frequencies) and amino acid foliar application of 0.00 ml/L (Null), 500 ml/L and 750ml/L were investigated. Water quality, soil properties plant height, fresh weight, fresh root weight, and yield count and yield weight measured. The plant growth parameters and yield are significantly responded to irrigation rates and to less degree to amino acid (biostimulant) .The interaction between treatments was significant at P<0.05. The application of amino acid at rate of 750 mg L-1 is relatively better but statistically insignificant. Such other parameters, Soil salinity effect, source of amino acid and application rates and time should be considered.